Intercultural matters of teaching Business English - Kovalchuk, Olga (My University, 2013)
The paper addresses the issue of the widely recognized role of intercultural matters while teaching Business English in 21st century. It is known that every time learners use Business English it is likely to be with someone from a different culture – they are involved in intercultural communication, thus they use specific language as well as certain techniques to get their message across. That is why they need some business communication skills along with Business English. The need of Intercultural Training is also emphasized and different approaches are discussed in this paper. In addition some key aspects in teaching Business English are analyzed: Sense of Purpose, Social Aspect, Clear Communication. Several approaches to identifying different dimensions as a method of analyzing and describing the nature of culture are discussed. This paper also deals with the significance of communicative competence. From the practical viewpoint two modern Business English books are mentioned, as they are well-tailored according Business English Students’ needs and used by us in the teaching process. It is concluded that Intercultural training should be an integral part of the Business English teacher’s job. У статті розглядається питання про широко визнану роль міжкультурних аспектів під час навчання ділової англійської в 21-му столітті. Відомо, що кожен раз, коли учні використовують ділову англійську вони, ймовірно, спілкуються з кимось з іншої культури - тобто беруть участь в міжкультурній комунікації, таким чином, вони використовують певну мову, а також деякі методи, щоб донести своє послання. Саме тому вони потребують навичок ділового спілкування поряд зі знанням ділової англійської мови. В статті окреслено необхідність міжкультурного навчання і різні підходи до його втілення.
Keywords: Intercultural training; communicative competence; business English; intercultural communication; business communication; міжкультурна підготовка; ділова англійська; комунікативна компетентність; міжкультурна комунікація; ділове спілкування; кафедра ділової іноземної мови та міжнародної комунікації